Economic, social and environmental impact of sustainable manufacturing: a Conceptual Study - Mastura, Roni; Juhaini, Jabar; Mariana, Yusoff; Mohd Razali, Muhamad (2013)

(untitled)
Sustainable manufacturing practices have rapidly evolved in the recent years. The efforts of manufacturing industries to achieve sustainable production have lead to the concern for economic, environment, and social impact in Malaysia. However, there is limited research conducted to uncover the specific sustainable manufacturing practices and impact among machining industry in Malaysia. Therefore, this paper intends to investigate the impact of sustainable manufacturing practices in the Malaysian machining industry. Based on a rigorous review of literature, this paper proposes a theoretical model to test the drivers affecting sustainable manufacturing practices and its impact on economic, environment and social well being. It also provides theoretical and practical implications into management perspectives and the impact of sustainable manufacturing practice towards triple bottom line in Malaysia.